EXPRESSIVE READING IN DEVELOPING ORAL AND WRITTEN SPEECH OF PRIMARY CLASS STUDENTS - Narzilloyeva Manzura Shuxrat qizi (International Journal of Innovations in Engineering Research and Technology, 2022)
This article discusses the importance of expressive reading in the development of native language-reading literacy of primary school students.